Growth Effects of Government Expenditure and Taxation in Rich Countries - Stefan Fölster; Magnus Henrekson (The Research Institute of Industrial Economics (IUI), 1998)
A number of cross-country comparisons do not find a robust negative relationship between government size and economic growth. In part this may reflect the prediction in economic theory that a negative relationship should exist primarily for rich countries with large public sectors. In this paper an econometric panel study is conducted on a sample of rich countries covering the 1970-95 period. Extended extreme bounds analyses are reported based on a regression model that tackles a number of econometric issues. Our general finding is that the more econometric problems are addressed, the more robust the relationship between government size and economic growth appears. Our most complete specifications are robust even according to the stringent extreme bounds criterion.
Keywords: E62; H20; H50; O23; O40; 330; Economic growth; extreme bounds analysis; government expenditure; public sector; taxation; cross-country regressions; panel regressions; robustness test; Öffentliche Ausgaben; Wirtschaftswachstum; Schätzung; Panelforschung; Industrieländer